An Experience of Using LMI Technique in Control Education*. Issue 6 (2016) - Pakshin, Pavel; Emelianova, Julia
Abstract: The LMI technique is very popular in modern control theory and applications due to powerful MATLAB-based LMI solvers and efficient interfaces provided by YALMIP package. This motivates wide application of this technique in control education. Nowadays, there exist good textbooks on the subject written for the graduate level but, in authors' opinion, a short course is needed for the undergraduate level. This course is preceded by the basic course on control theory. In this paper, the authors' experience of developing a short course is described. The sketch and most important issues of this course are also presented.